H i constraints from the cross-correlation of eBOSS galaxies and Green Bank Telescope intensity maps. Issue 3 (13th December 2021) - Wolz, Laura; Pourtsidou, Alkistis; Masui, Kiyoshi W; Chang, Tzu-Ching; Bautista, Julian E; Müller, Eva-Maria; Avila, Santiago; Bacon, David; Percival, Will J; Cunnington, Steven; Anderson, Chris; Chen, Xuelei; et al.
ABSTRACT: We present the joint analysis of Neutral Hydrogen (H i ) Intensity Mapping observations with three galaxy samples: the Luminous Red Galaxy (LRG) and Emission Line Galaxy (ELG) samples from the eBOSS survey, and the WiggleZ Dark Energy Survey sample. The H i intensity maps are Green Bank Telescope observations of the redshifted 21cm emission on 100 deg^2 covering the redshift range 0.6 < z < 1.0. We process the data by separating and removing the foregrounds present in the radio frequencies with FastI ICA . We verify the quality of the foreground separation with mock realizations, and construct a transfer function to correct for the effects of foreground removal on the H i signal. We cross-correlate the cleaned H i data with the galaxy samples and study the overall amplitude as well as the scale dependence of the power spectrum. We also qualitatively compare our findings with the predictions by a semianalytical galaxy evolution simulation. The cross-correlations constrain the quantity Ω _H I b_H I r_H I, opt at an effective scale k eff, where Ω _H I is the H i density fraction, b_H I is the H i bias, and r_H I, opt the galaxy–hydrogen correlation coefficient, which is dependent on the H i content of the optical galaxy sample. At k_eff=0.31 h Mpc^-1 we find Ω _H I b_H I r_H I, Wig = [0.58 ± 0.09 (stat) ± 0.05 (sys)] × 10^-3 for GBT-WiggleZ, Ω _H I b_H I r_H I, ELG = [0.40 ± 0.09 (stat) ± 0.04 (sys)] × 10^-3 for GBT-ELG, and Ω _H I b_H I r_H I, LRG = [0.35 ± 0.08 (stat) ± 0.03 (sys)] × 10^-3 for GBT-LRG, at z ≃ 0.8. We also report results at k_eff=0.24 and k_eff=0.48 h Mpc^-1 . With little information on H i parameters beyond our local Universe, these are amongst the most precise constraints on neutral hydrogen density fluctuations in an underexplored redshift range.